Investment Criteria, Productivity, and Economic Development: Comment - Villard, Henry H. (Quarterly Journal of Economics, 1957)
Journal Article Investment Criteria, Productivity, and Economic Development: Comment Get access Henry H. Villard Henry H. Villard Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 71, Issue 3, August 1957, Pages 470–471, https://doi.org/10.2307/1884670 Published: 01 August 1957